Development of Digital Leaflet Learning Media Based on Pancasila Student Profiles (P3) in the Pancasila Education Subject for Class IV at SDN 164 Palembang - Rahmasari, Fani; Aquami, Aquami; Shawmi, Ayu Nur (FKIP - Universitas Riau, 2025)
This study discusses the limitations of technology-based learning resources and the low interest of students in understanding abstract concepts in the Pancasila Education subject. The purpose of the study was to develop and evaluate digital leaflet learning media based on the Pancasila Student Profile for fourth-grade students of SDN 164 Palembang. The study used a research and development (R&D) method with the ADDIE model, involving 1 teacher and 10 students as samples. Data were collected through observation, interviews, questionnaires, and documentation, and analyzed using validity and practicality tests. The results showed that the media obtained an average validity score of 83.79% (very valid) and a practicality score of 92.4% (very practical). The results showed that the developed digital leaflet media effectively increased learning interest, facilitated understanding of abstract concepts, and supported character formation according to the Pancasila Student Profile. In conclusion, the digital leaflet media is feasible and practical to use in the learning process; however, further development is still recommended to improve interactivity, content quality, and wider implementation in various educational environments.